51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-187
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Gas-Surface Interactions for High-Enthalpy Reacting Flows

Abstract: The aerothermal heating of a Thermal Protection System (TPS) is significantly affected by the physical and chemical interactions that occur between the planetary entry vehicle surface and the hypersonic atmospheric gas. To study these processes, a gas-surface interaction model is used in the present numerical analysis that accounts for surface catalytic reactions and surface participating reactions. The study examines the effects of gas-surface interactions for graphite exposed to high enthalpy reacting nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Likely, the nitridation coefficient is small, leading to a minimal impact on the simulation when nitridation is excluded. Recent results have also shown that the nitrogen-atom recombination reaction occurring at the surface of hot graphite is very fast [35,36]. For the tested cases, the nitrogen-atom concentration at the surface is only significant near the stagnation point, which is away from the flow instability studied.…”
Section: Surface-chemistry Modelmentioning
confidence: 80%
See 1 more Smart Citation
“…Likely, the nitridation coefficient is small, leading to a minimal impact on the simulation when nitridation is excluded. Recent results have also shown that the nitrogen-atom recombination reaction occurring at the surface of hot graphite is very fast [35,36]. For the tested cases, the nitrogen-atom concentration at the surface is only significant near the stagnation point, which is away from the flow instability studied.…”
Section: Surface-chemistry Modelmentioning
confidence: 80%
“…If the derivative operators of Eqs. (33) and (35) are applied to a centered stencil in computational space, the standard central finite difference coefficients are obtained. In other words, the fourth-order method used by previous researchers for interior points can be obtained from the current method using a five-point stencil in computational space.…”
Section: High-order Lst Numerical Methodsmentioning
confidence: 99%